Penguatan Kapasitas Adaptasi Generasi Z Pedesaan Dalam Menghadapi Variabilitas Iklim - Nurdin, Ibnu Phonna; Fatia, Dara; Mustaqim, Mustaqim; Simanjuntak, Asnika Putri; Keumalawati, Cut; Rusnawati, Rusnawati; Al Zuhri, Al Zuhri (Yayasan Inspirasi El Burhani, 2024)
Introduction: The climate variability that occurs in Indonesia results in various losses for society, especially in rural areas. Rural communities whose livelihoods depend on agricultural and fishing activities are very threatened by climate variability which hampers the community's economy. Objective: This service aims to analyze participation in strengthening the adaptation of rural Generation Z in facing climate variability Method: The focus of community service in this activity is the Z generation who live in rural areas. To make it easier to provide information to generation Z. A participatory approach is used in this activity. Result: There are 3 main activities in strengthening adaptation capacity for generation Z, namely: 1. Introduction stage, including a basic understanding of several forms of climate variability that occur in rural areas. 2. Advanced stage, namely providing education regarding the impact of climate variability in rural areas, especially agriculture and fisheries, 3. Adjustment stage, namely developing adaptation strategies that must be carried out when exposure to extreme climate variability occurs. Conclusion: The results of this service show an increase in generation Z's knowledge in anticipating climate variability.